(3GdMeGjI GdbGfhfjI GdGSe GdJLGQj (B/s - (3Gdabi, YGWa eMeOs ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2001)
(3TQhW GdMeGjI GdbGfhfjI ddGSe GdJLGQj bhGYO GNJjGQ GdGSe GdJLGQj , WQb GcJSGH GdMb aj GdGSe GdJLGQj fWGb GdMeGjI GdMeGjI GdbGfhfjI ddGSe GdJLGQj MeGjI GdGSe GdJLGQj aj ehGLgI GdGSe GdJLGQj ddZjQ , MeGjI GdGSe GdJLGQj aj GdehGLgI GdJLGjI GdYdGeI ddZjQ , MeGjI GdGSe GdJLGQj aj MGdI GdJUQa ajg CdjGJ GdMeGjI GdbGfhfjI ddGSe GdJLGQj GdMeGjI GdYGeI ddGSe GdJLGQj , GdMeGjI GdNGUI ddGSe GdJLGQj , GdMeGjI GdOhdjI ddGSe GdJLGQjs
(3HjHdjhZQGajG (B: (3U(B. 178 (3; bGFeI GdeNJUQGJ(B: (3U(B. 188s
Keywords: (3GdGSe GdJLGQjs; (3GdYdGeI GdJLGQjI(B- (3bhGfjf h JTQjYGJ s